Time-varying three-dimensional interferometric imaging for space rotating targets with stepped-frequency chirp signal - Sun, Yuxue; Luo, Ying; Zhang, Qun; Hu, Jian; Huo, Wenjun (IET radar, sonar & navigation, 2017)
Three-dimensional (3D) radar imaging can provide abundant information about space targets, thus playing a significant role in space target recognition, measurement and cataloguing. In this study, a time-varying interferometric 3D imaging method for space rotating targets is proposed based on stepped-frequency chirp signal. In this study, with L-shaped three-antenna configuration, the interferometric signal model is first set up and high-resolution range profile (HRRP) series of the three antennas are obtained. Then through interferometric processing of HRRP series on different interferometric planes, the instantaneous spatial positions in the azimuth and pitching directions of each target scatterer are reconstructed. Combining with the instantaneous positions in range direction extracted from HRRP series, the time-varying 3D image of target can be reconstructed accordingly. Compared to existing 3D imaging method for space rotating targets, the proposed method can obtain real time-varying 3D image of target with one multi-antenna set radar. Simulation results verify the validity and robustness of the proposed method.